Pengaruh Motivasi Terhadap Kinerja Pegawai Pada Dinas Pertambangan Dan Energi Kab. Kutai Kartanegara - Umar, Nasir (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
The motivation effect to the employee work at mining department in department of mining and energy of Kutai Kartanegara Regency, according to the research result and data analysis result can be known theoretically to know account result with product moment correlation formula gotten correlation score as 0.933. this result include into very strong interpretation category, according to the interpretation table of correlation score, the account result can be concluded that there is positive and significant relation between motivation variable and employee ability variable to the Department of mining and energy of Kutai Kartanegara that motivation has effect to the employee work in Department of mining and energy of Kutai Kartanegara Regency accepted because of the truth has been proven. Kata Kunci : Motivation, Works